Vitamin D Deficiency in Children/Adolescent Presenting with Night Time Legs Pain - Naheem Ahmed, Kiran Ashfaq Ahmed, Tayyaba Siddique, Raja Imtiaz Ahmed, Muhammad Aftab, Rashada Bibi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of vitamin D deficiency in children/adolescent presenting with night time leg’s pain at Sheikh Khalifa Bin Zayed Al Nahyan Hospital Ak CMH Muzaffarabad. Methodology: This was a cross-sectional study, which was conducted at the pediatric Department SKBZ/CMH Muzaffarabad, during six months from July 2021 to December 2021. All the adolescent children presented with leg’s pain during sleep at night and both genders presenting at paediatric OPD were included. After obtaining informed consent, a 3ml blood ample was obtained from each case and immediately sent to the Hospital diagnostic laboratory to assess the vitamin D level. All demographic information, including vitamin levels, were documented via study proforma and SPSS version 26 was used to enter and analyze all of the data. Results: A total of 60 adolescent children who presented with leg’s pain were studied to observe their vitamin D levels and their average age was 05.93+2.94 years. Out of all, 40 (66.7%) cases were males and 20 (33.3%) were females. Only two children were found with normal vitamin D level, and from all of the remaining 50.0% had vitamin D deficiency (<20 ng/mL) and 46.7% had insufficiency (20–30 ng/mL). Vitamin D deficiency was statistically significant according to age (p-0.006), whereas it was statistically insignificant according to gender (p-0.117). Conclusion: Vitamin D deficiency was observed to be higher among almost all the cases presented with leg’s pain during the night. This was an alarming situation to our current generation. According to these findings, it is estimated that vitamin D deficiency increases with increasing age.